2008
DOI: 10.1159/000149818
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Schizophrenic Patients Switched from Typical Antipsychotic Agents to Amisulpride and Olanzapine

Abstract: Schizophrenia is a severe mental disorder that requires lifelong treatment, and therefore information on the cardiovascular safety and tolerance of antipsychotics is of significant clinical importance. Atypical antipsychotics have been used to treat schizophrenia patients since the 1990s, and more and more patients have been switched to these from typical antipsychotics; however, there is still no accessible evaluation tool for assessing cardiovascular safety. In this study, we used a computer-assisted 5-min m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
1
11
0
2
Order By: Relevance
“…Previous studies have revealed that clozapine has an inhibitory effect on HRV, 30,32 whereas amisulpiride produces a higher HF than olanzapine after switching from a typical antipsychotics. 41 Our results are compatible with these studies and go further by pointing out that other antipsychotics with an HMA (or so-called dirty drugs) also have an effect of parasympathetic inhibition. Among these antipsychotics, the muscarinic affinity is much higher than the nicotinic affinity.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have revealed that clozapine has an inhibitory effect on HRV, 30,32 whereas amisulpiride produces a higher HF than olanzapine after switching from a typical antipsychotics. 41 Our results are compatible with these studies and go further by pointing out that other antipsychotics with an HMA (or so-called dirty drugs) also have an effect of parasympathetic inhibition. Among these antipsychotics, the muscarinic affinity is much higher than the nicotinic affinity.…”
Section: Discussionsupporting
confidence: 89%
“…Duplicates were removed, titles and abstracts scanned, potential articles read and evaluated against inclusion criteria and authors contacted for additional data when necessary. In total, 140 case-control and 30 treatment 76,83,93,110,116,129,138,141,155,175,[187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] studies were eligible for inclusion in the quantitative synthesis (151 case-control and 43 effect sizes for analysis); 10 of the studies were included in both the case-control and treatment analyses. 76,83,93,110,116,129,138,141,155,175 Four subgroups of disorders (mood, anxiety-related, psychotic and substance dependence disorders) and 2 classes of psychotropic medications (antidepressants and antipsychotics) were included.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Further, Mathewson et al (2012) found that clozapine-treated patients displayed both poorer performance on the WCST and lower levels of parasympathetic activity relative to schizophrenia patients treated with other antipsychotic medications. Similarly, Wang et al (2008) examined schizophrenia patients who were switched from typical antipsychotic medication to either amisulpride or olanzapine. Parasympathetic activity improvements were observed in patients who were transitioned to amisulpride versus olanzapine.…”
Section: Antipsychotic Medication and Hrvmentioning
confidence: 99%